PQ improvement of Micro-Grid by Using DG and Power Quality Conditioner with BESS - Sekhar Mishra, Chandra; Kumar Jena, Ranjan; Ranjan Nayak, Soumya (International Journal of Engineering and Technology, 2018)
DG Grid interfaced system has been focused through this paper. The objective is to improve power quality of the grid, which was polluted by various means. The improvement of power quality of the micro grid includes uses of a specially designed DG, BESS and Power Quality conditioner. The system consists of a two-stage power conversion. Solar PV supplies power for both DC and AC loads. Manufacturer datasheet is used for modeling the PV panel. In order to keep the BUS voltage stable a BESS is joined to DC BUS through power electronic converter, which is used to absorb the excess power whenever production is high and deliver power to the load on low production. The system continues to supply the local loads, incase of grid discontinuity. Thus it eliminates threats of islanding. This paper also focuses on control and stability of DC bus voltage and energy management scheme. The project uses Matlab/Simulink platform for efficient verification. For power quality improvement of Micro Grid it uses 3leg inverter, which is coupled with SPV and MPPT with Battery storage, which is used as compensator for the whole system. For prevention to reduce voltage current and power flow between DG and Grid, it is necessary to have an optimum control. Through the adjustment of power circulation between shunt paired DG ensures current voltage and power on micro grid. +ve, -ve and Zero sequence components of currents and voltage can be adjustedÂ Â by the suggested methodology in Grid tied DG system. The said PQC have multiple uses. Firstly as a power converter and secondly as a shunt APF for harmonic compensation on voltage, current and power (both active and reactive) for both balanced and unbalanced loads in the Grid tied DG system. It also cares for the neutral conductor. Either individually or in grid connected mode all the above objectives can be achieved. For the entire Grid, it is realized that after compensation three phase four wired un-balance loads looks as balanced linear resistive load for the Grid. All these task significantly replicated on MATLAB/Simulink. After compensation the total harmonic distortion on input voltage and current reduced drastically. IEEE519 in the range of 5% suitably accepts it. Â